2022
DOI: 10.1039/d2sm00947a
|View full text |Cite
|
Sign up to set email alerts
|

A particulate blood analogue based on artificial viscoelastic blood plasma and RBC-like microparticles at a concentration matching the human haematocrit

Abstract: There has been an enormous interest in the production of fluids with rheological properties similar to those of real blood over the last years. Application fields range from Biomicrofluidics (microscale)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…9). The stability of the properties of our material over the course of 12 weeks has a comparable shelf-life to other synthetic blood materials 18 and can be stored at room temperature – enhancing its accessibility. The surface tension of the FBS did rise over the tested time interval but was shown to decrease again at 4 weeks (Table 3).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…9). The stability of the properties of our material over the course of 12 weeks has a comparable shelf-life to other synthetic blood materials 18 and can be stored at room temperature – enhancing its accessibility. The surface tension of the FBS did rise over the tested time interval but was shown to decrease again at 4 weeks (Table 3).…”
Section: Resultsmentioning
confidence: 95%
“…; 3,12 aqueous Acrysol and dye material; 13 silicon solution-gelation (sol-gel) materials; 14,15 hyaluronate and amino acid containing materials; 16 to emulsion-based materials using styrene and polyvinylpyrrolidone (PVP) 17 or polydimethylsiloxane (PDMS) microparticles. 18 The available commercial blood materials have limited rheological properties and bloodstain features in comparison to human blood, 15,16 limiting their use in BPA research and training. Recent FBS research describes materials that contain multi-functional and/or multi-component structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Although the Hb concentration is lower than the normal physiological range (around 16 g dL À1 ), the obtained Hb content in the present workflow is in the same range as the Hb content of 4.2 g dL À1 reported for Hb conjugated to PEG of the MP4 oxygen carrier product. 56 Further development of our proof-of-concept process to develop a RBC substitute should expand on the stability of the components beyond the one-week initial tests included here and tuning of mechanical properties to accommodate rheological properties mimicking whole blood 57,58 and support of circulation times as well as testing of biocompatible properties. More specific, the Ca-alginate materials are obtainable with different mechanical moduli by the selection of alginate molecular mass, alginate type, and concentration, as well as the concentration of Ca 2+ .…”
Section: Performance Of Suggested Fabrication Route and Resulting Hb ...mentioning
confidence: 99%
“…Recent studies have shown that pro-inflammatory and oxidative states or nutritional deficiency also induce RBC fragmentation with release of microparticles into the blood [ 68 ]. In particular, RBC microparticles contain molecules capable of activating various processes, mainly negative, in other cells such as WBCs, platelets, and endothelial cells, leading to an increase in the pro-inflammatory, pro-thrombotic, and oxidative state, and anisocytosis.…”
Section: Pathophysiological Mechanisms Of Increased Rdwmentioning
confidence: 99%